Tantric Elements in Balinese Hindu Rituals - Ida Bagus Putu Suamba (Universitas Udayana, 2025)
Ritual forms an integral part of Balinese life; however, most Balinese do not realize that the ritual they practice is a blend of Vedic and Tantric elements expressed in local culture. This research aims to highlight the Tantric aspects of Balinese religion, which are usually mislabeled as mere Vedic rituals. A qualitative methodology was employed to analyze textual traditions and ritual practices. Data was collected, categorized, and analyzed to address the main elements of Tantray?na worship and how they are present in Balinese ones. Ubiquitous ritual elements such as ma??ala, yantra, pañca mak?ra, ak?ara and scales based on the human body are from the Tantra tradition. This article explores these individually, along with the generic structure of Balinese Hindu rituals.